The Relationship between Coping Strategies and Stress Levels among Undergraduate Nursing Students - Barkah, Risman; Syiddaturrohmah, Nazwa Siti (Inspirasi Foundation, 2026)
Introduction: Nursing students commonly experience high levels of stress during clinical practice in hospital settings. This stress is often caused by academic pressures, complex clinical tasks, time constraints, and the need to adapt to professional responsibilities in real healthcare environments. Coping strategies are considered an important factor that may influence how nursing students respond to stressful situations during clinical practice. Objective: This study aimed to determine the relationship between coping strategies and stress levels among undergraduate nursing students during clinical practice in hospitals. Method: This study employed a descriptive correlational design with a cross-sectional approach. The sample consisted of 33 sixth-semester undergraduate nursing students selected using a total sampling technique. Data were collected using validated questionnaires to measure coping strategies and stress levels. Bivariate analysis was conducted using the chi-square test with a significance level of 0.05. Result: The findings showed that the majority of respondents were female (57.6%) and above the average age (63.6%), with all participants enrolled in the sixth semester. Among students with poor coping strategies, 15 respondents (60%) experienced mild stress, while 5 respondents (71.43%) experienced moderate stress. Statistical analysis using the chi-square test revealed a p-value of 0.581, indicating that there was no statistically significant relationship between coping strategies and stress levels among nursing students during clinical practice (p > 0.05). Conclusion: This study concluded that there is no significant relationship between coping strategies and stress levels among undergraduate nursing students during clinical practice in hospitals. These results suggest that stress experienced by nursing students may be influenced by various factors beyond individual coping strategies. Therefore, a holistic approach involving academic support, effective clinical supervision, and psychological interventions is recommended to help nursing students manage stress more effectively.